2018
DOI: 10.1021/acssuschemeng.8b00512
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid of g-C3N4 and MoS2 Integrated onto Cd0.5Zn0.5S: Rational Design with Efficient Charge Transfer for Enhanced Photocatalytic Activity

Abstract: Rational design of hierarchical nanocomposites is a promising approach for efficient energy harvesting and conversion. A noble-metal-free ternary hierarchical composite, Cd0.5Zn0.5S-g-C3N4-MoS2, has been developed. Materials were chosen based on their relative band-edge alignments and they were studied as a composite for photocatalytic properties. The photocatalytic activity was evaluated by measuring the rate of photodriven H2 evolution with concomitant degradation of organic pollutants, such as Rhodamine B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 75 publications
(113 reference statements)
0
18
0
Order By: Relevance
“…41–1049 and 36–1450) . In ternary Cd x Zn 1‐x S composites, peaks are shifted gradually to a larger incident angle, indicating the probability of formation of a homogenous alloy from the elemental composition . The absence of additional peaks in the diffraction patterns confirms phase singularity for Cd x Zn 1‐x S composites.…”
Section: Resultsmentioning
confidence: 84%
“…41–1049 and 36–1450) . In ternary Cd x Zn 1‐x S composites, peaks are shifted gradually to a larger incident angle, indicating the probability of formation of a homogenous alloy from the elemental composition . The absence of additional peaks in the diffraction patterns confirms phase singularity for Cd x Zn 1‐x S composites.…”
Section: Resultsmentioning
confidence: 84%
“…In order to investigate the band structure of Cd 0.5 Zn 0.5 S and Ni 2 P@Cd 0.5 Zn 0.5 S–5 %, Mott–Schottky curves of the two materials were measured. As was shown in Figure , the positive slope of the Mott–Schottky curves indicated both of them belonged to n–type semiconductors . Flat‐band potentials of Cd 0.5 Zn 0.5 S and Ni 2 P@Cd 0.5 Zn 0.5 S–5 % were –0.32 and –0.28 V, respectively.…”
Section: Resultsmentioning
confidence: 71%
“…Recent reports have shown that loading of g‐C 3 N 4 and MoS 2 on Cd 0.5 Zn 0.5 S and using Na 2 S as electron donor resulted in enhanced quantum yields of hydrogen evolution reaction . The introduction of two semiconductors g‐C 3 N 4 and MoS 2 into Cd 0.5 Zn 0.5 S could be conductive to the separation of electron and holes, and promote the oxidation reaction of hole and reduction reaction of electron.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of a solid-solution strategy is to improve the redox ability of a pristine semiconductor and/or the capacity of the optical absorption, which can be favorable for the photocatalysis. Therefore, numerous photocatalysts with an outstanding performance, such as GaN:ZnO, BixY1-xVO4, ZnIn2S4, and ZnxCd1-xS, have been successfully designed by applying this strategy [28][29][30][31][32][33][34][35]. ZnxCd1-xS series materials have received significant interest for use in the photocatalytic hydrogen evolution.…”
Section: Introductionmentioning
confidence: 99%